Diskursus Demokrasi Deliberatif Dalam Membina Hubungan Wakil Rakyat Dan Konstituen Pasca Pemilihan Umum - Dasul Santoso (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
The dynamics of the relationship between people's representatives and constituents today cannot only be interpreted in the stages before and when general elections are held, but needs to be understood as a whole, especially regarding how guaranteeing the implementation of the goals of post-election representative democracy ends in fostering relations between people's representatives and constituents. The discussion in this study focuses on fundamental questions about the influence of the responsibilities of representatives of the people to constituents after the election on public trust which is then elaborated with the application of the concept of deliberative democracy. This research method is carried out using a doctrinal approach. The results of the study describe that in the implementation of representative democracy in Indonesia, there is a democratic deficit which causes distrust of representative institutions due to policy configurations that are considered elitist and unresponsive. With the approach of applying the concept of deliberative democracy, it can be an alternative in solving problems between people's representatives and constituents through mutual agreement in determining policy directions.